TalTech journal of European studies - Tallinna Tehnikaülikool. Õiguse instituut (De Gruyter Poland, 2020)
"Since 2020, the scope of the journal is related to digitalisation and technology implementation and their impact in the social, legal, political, economic and cultural domains in the European Union and its Member States."
Keywords: European Union : Periodicals; European Union; Technology and law : European Union countries : Periodicals; Law : European Union countries : Periodicals; Droit : Pays de l'Union européenne : Périodiques; Technology and law; Law; Europe : Periodicals; Europe : Périodiques; Europe; European Union countries